MISSION ENTREPRENEURSHIP: A SYSTEMATIC LITERATURE REVIEW AND RESEARCH AGENDA - Desiana Nainggolan; Rio Janto Pardede (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
This study aims to provide guidance in the theoretical development of mission entrepreneurship through a Systematic Literature Review and provide an overview of the situation when the research is carried out, as well as discover the gap for further research. The results of the review found answers to research questions, namely that previous studies were more dominant in discussing mission entrepreneurship only as a concept. Based on the review, the research types that are still rarely used are quantitative and mixed-methods. Responses from respondents or researchers are more directed to the concept of mission entrepreneurship. The understanding of mission entrepreneurship is not comprehensive enough. The previous article did not discuss the biblical text as the theological basis for mission entrepreneurship. The geographical distribution (country) analysis, which became the subject and object of research, was more dominant in Indonesia, followed by America. The Church and missionaries more widely use the impact of the research results in the mission field. As for the mission strategy and the mission agency itself, it does not have a significant effect. Therefore, this Systematic Literature Review research is expected to guide and map future mission entrepreneurship theory development.